PP.32.28: A NEW INDEX INCLUDING PULSE PRESSURE COULD IMPROVE PREDICTIVE VALUE OF BP RESPONSE TO EXERCISE. (June 2015) - Vaisbuj, F.; Sabate, D.; Perea, M.; Spernanzoni, F.; Lanfranco, C.; Obregon, S.; Koretzky, M.; Dulude, E. Perasso; Huguet, E.; Kotliar, C.
Abstract : Objective: Previous studies have shown a link between elevated pulse pressure and an exaggerated increase in SBP related to exercise thought to be at least partially due to arterial stiffness. Otherwise, in general practice cardiovascular behavior on exercise is evaluated by the SBP x HR response while DBP is not considered useful because of its low reproducibility. Based on this, we proposed a new index including pulse pressure as more representative of buffer properties of vascular tree and cardiac pulsatility. To evaluate association between cardiovascular response to exercise and arterial stiffness by determining the efficacy of a new index (HR x PP exercise)- (HR x PP rest). Design and method: We evaluated 120 consecutive patients performing maximal treadmill stress test, and non invasive screening of vascular condition measuring augmentation aortic index, PWV, Central Aortic Pressure, Central Pulse Pressure. Results: After exclusion criteria (diabetes, non controlled hypertension, not satisfactory stress test, arrhythmias, use of beta-blockers drugs, previous cardiovascular major events or known coronary heart disease), final cohort consisted in 64 pts (normotensives (26), controlled hypertensive (38), males (50%), age 55.09 ± 26.5 yo). We stratified them by age tertiles: a) 25–45, b)45–65 c)older than 65. Resting ITT (HR x Systolic Arterial Pressure) was associated to PWV in older group (p < 0.001), while the proposed new index (HR x PPexercise)- (HR x PPrest) showed its maximal efficacy (67%) for predicting arterial stiffness in intermediate age group (<0.0001). HR x PP rest was associated with CAP (p = 0, 038) and with PWV with good efficacy in older group (>65yo). Those findings were independent of hypertensive condition at rest. Conclusions: Considering pulse pressure changes during exercise probed to improve BP predictive value for the risk of atherosclerosis in primary prevention subjects. Large scale studies on each age group are needed in order to better identify de best predictor for each one. Exercise stress test is a simple and worldwide used method that could improve its stratification power for predicting subclinic atherosclerosis beyond coronary heart disease detection.